2021
DOI: 10.1161/atvbaha.120.315644
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea, Sleep Duration, and Associated Mediators With Carotid Intima-Media Thickness

Abstract: Objective: To elucidate the independent associations of obstructive sleep apnea (OSA) and sleep duration (SD) as well as the potential inflammatory and metabolic mediators on carotid intima-media thickness (CIMT) in a large cohort of adults. Approach and Results: Consecutive participants from the ELSA-Brasil performed a clinical evaluation, sleep study, 1-week actigraphy for defining SD and CIMT using standard techniques. Gamma regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 48 publications
0
9
0
5
Order By: Relevance
“…OSA causes endothelial dysfunction ( Hoyos et al, 2015 ; Khalyfa et al, 2016 ), unstable plaque characteristics ( Trzepizur et al, 2014 ; Konishi et al, 2019 ), and atherosclerosis ( Wattanakit et al, 2008 ; Ma et al, 2016 ; Zhou et al, 2017 ). Recently, one of the largest studies in this area to date ( n = 2009) found that OSA is independently associated with increased carotid intima-media thickness in a dose-responsive manner ( Souza et al, 2021 ), reinforcing the role of OSA as a potential nontraditional risk factor for atherosclerosis.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…OSA causes endothelial dysfunction ( Hoyos et al, 2015 ; Khalyfa et al, 2016 ), unstable plaque characteristics ( Trzepizur et al, 2014 ; Konishi et al, 2019 ), and atherosclerosis ( Wattanakit et al, 2008 ; Ma et al, 2016 ; Zhou et al, 2017 ). Recently, one of the largest studies in this area to date ( n = 2009) found that OSA is independently associated with increased carotid intima-media thickness in a dose-responsive manner ( Souza et al, 2021 ), reinforcing the role of OSA as a potential nontraditional risk factor for atherosclerosis.…”
Section: Introductionmentioning
confidence: 96%
“…Atherosclerosis is the pathological basis of peripheral arterial disease, coronary heart disease, and stroke. In addition to traditional risk factors such as hereditary susceptibility, aging, hypertension, obesity, diabetes, and smoking, obstructive sleep apnea-hypopnea syndrome (OSA) that affect up to 100 million people worldwide has emerged as a new significant and independent risk factor for atherosclerosis ( Ali et al, 2014 ; Souza et al, 2021 ). OSA is characterized by repetitive episodes of hypopnea or apnea due to upper airway collapse during sleep ( Lévy et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the coronary atherosclerotic plaque ( 17 ) and its IMT were significantly positively correlated with AHI severity ( 18 ). In a recent large cohort of 2009 participants, OSA was independently associated with the increased carotid IMT in a dose-response relationship, and this association was partially mediated by inflammation and dyslipidemia ( 19 ). Also, treatment with continuous positive air pressure (CPAP) which is an effective treatment of OSA, significantly improved early signs of atherosclerosis, such as IMT and pulse-wave velocity ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…A duração objetiva do sono foi realizada usando o actigrafo de punho Actiwatch 2™ (Philips-Respironics®) (Figuras 7 e 8). 58,59 Para análise da DS, apenas indivíduos com 7 dias válidos foram incluídos para permitir a amostragem de dias uteis e não uteis. aproximadamente dois terços da amostra do nosso estudo.…”
Section: Actigrafia De Pulsounclassified
“…58 A DS curta e longa foram definidas como <6 e >8 horas, respectivamente. 58,59 Critérios semelhantes foram usados por outros investigadores. 60 Calculamos o tempo de vigília após o início do sono (WASO), definido pelos períodos de vigília que ocorrem após o início do sono definido.…”
Section: Actigrafia De Pulsounclassified